Examining The Attitudes Of Amateur Football Players Towards Football - Nuh Asanakut; Gökhan Dokuzoğlu; Mehmet Özdemir; Erhan Buyrukoğlu (Türk Spor ve Egzersiz Dergisi)
In this study, it is aimed to examine the attitudes of amateur football players towards football. The study group of the research consists of 194 football players who play football actively in Sivas and Yalova provinces in the 2021-2022 season. Data collection in the study consists of two parts. In the first part, the personal information form created by the researchers was used, and in the second part, the Football Attitude Scale (FUTÖ) scale, which Kayapınar and Kaan's validity and reliability were made (2021), was used. In the analysis of the data in this study, the SPSS 25.00 package program was used, and it was evaluated at the 95% confidence interval and at the 0.05 significance level. Descriptive statistics were calculated regarding age, gender, educational status, geographical region, province and the position information of the participants in football. It was decided whether the data showed a normal distribution or not by looking at the kurtosis skewness values. In terms of statistics, Independent Sample t test, Anova test, frequency, percentage and reliability coefficient calculations were made. As a result; When the attitudes of the participants towards football in the gender variable are examined, there is a statistically significant difference in favor of the female participants between the scale total score and the sub-dimensions of the scale, social effects, performance, and psychological effects. It was seen that there was a statistically significant difference in the sub-dimensions, and there was no statistically significant difference between the province and location variables, the total score of the scale and all sub-dimensions.